A Power Amplifier Modeling Method Based on the Time Delay Deep Neural Network - Wang, Shilin; Liu, Wenyuan (Journal of Research in Science and Engineering, 2025)
A power amplifier (PA) modeling method based on the time delay deep neural network (TDDNN) is proposed in this paper. By integrating time-delay units with a multi-layer hidden neural network structure, the TDDNN enhances the modeling capability for dynamic nonlinear systems. Time-delay information and a multi-layer network architecture are incorporated into the TDDNN to improve its ability to capture the memory effects and nonlinear characteristics of input signals, thereby increasing modeling accuracy. Meanwhile, the number of hidden layer neurons in TDDNN is reduced, which optimizes the structural complexity of the model. The feasibility of this innovative structure is demonstrated through a case study of a Motorola PA. Experimental validation indicates that the proposed TDDNN method not only improves modeling accuracy but also effectively reduces computational complexity, offering an efficient solution for modeling complex dynamic nonlinear systems.